Tangguoa gen. nov., one new genus of daddy-long-leg spiders (Araneae: Pholcidae) from southern China - Yao, Zhiyuan; Luo, Yiping; Li, Shuqiang (Zootaxa, 2021)
The spider family Pholcidae C.L. Koch, 1850 exhibits high diversity at generic level and currently contains 94 genera. In this study, one new genus Tangguoa Yao & Li gen. nov. from southern China is described with the type species T. laibin Yao & Li sp. nov. (male, female; Guangxi) and one additional species T. tongguling Yao & Li sp. nov. (male, female; Hainan).